Alarm triggered multiple display thermometer using MC68HC11 - Ahmad Firdaus, Makhtar (2008)
The alarm triggered multiple display thermometer is a digital thermometer using microcontroller MC68HC11 and the output will display through LCD and Visual Basic. This project consist the design, programming development, and evaluation of the digital thermometer. It consist the module of the temperature sensor, LCD, control switch, buzzer which integrated with 8-bits microcontroller MC68HC11. The temperature sensor will measure the temperature in range from 0°C to 100°C and the buzzer will triggered if temperature is equal or higher than set temperature. Besides that, the system can store the maximum and minimum temperature in RAM. From Visual Basic, user can save all the data displayed.